Individual-group discontinuity from the differing perspective of Campbell's realistic group conflict theory and Tajfel and Turner's social identity theory - Insko, Chester A.; Schopler, John (1992)
Two experiments investigated the implications of realistic group conflict theory and social identity theory for explaining the individual-group discontinuity effect. We interpreted realistic group conflict theory as directly implying that individual-group discontinuity is motivated by competition for valued outcomes (max own); we interpreted social identity theory as suggesting that individual-group discontinuity is motivated by relatives social comparisons 9 max rel). We developed a new three-choice matrix to differentiate max own from max rel competitiveness. Experiment 1 revealed that groups selected more own and more max rel than did individuals. Experiment 2 enabled a more careful examination of the development of max rel. The results show that max rel emerged only after some experience with competitive relations, and that one reason for the initial reluctance to select max rel was the associated own sacrifice. We interpreted the results further as implying that max rel is perceived initially as inappropriately confrontation. Although "mere" categorizing will not produce max rel, max rel will occur if a category of subjects has experienced inter-category (or inter-group) competitiveness.